“Might a spouse’s personality and support influence one’s workplace performance?”: The role of housework engagement in work productivity despite presenteeism. - Correia Leal, C.; Ferreira, A.I. (European Conference of Personality 2020, 2022)
The present study is one of the first to investigate the effects of housework engagement on work productivity despite presenteeism and to explore personality traits (i.e. conscientiousness) and gender differences among couples. Based on a sample of 180 Portuguese heterosexual couples, an integrated model of both housework and workplace realities was proposed and tested. Hypotheses testing was based on the actor-partner interdependence model using structural equation modeling. The results verify that the higher the degree of women’s conscientiousness, the greater their and their partners level of productivity despite presenteeism. In addition, the higher the couple’s perception of partner support is, the greater their level of work productivity despite health problems, for both men and women. Results also confirm that housework engagement mediates the relationships between both conscientiousness and perceived partner support and work productivity despite health problems, for women, but not for men. This study denotes an advance in the literature on the relationships between personal and social resources within the family domain and work productivity despite presenteeism and addressed the possibility of “good” presenteeism. The findings provide support for the applicability of the J-DR model to housework and show that the availability of personal and social resources can enable individuals to deal with demanding tasks at home and at work.